Cyclic thermal performance analysis of a traditional Single-Layered and of a novel Multi-Layered Packed-Bed molten salt Thermocline Tank. (April 2018) - Li, Meng-Jie; Qiu, Yu; Li, Ming-Jia
Abstract: In the study, a transient, two-dimensional and axisymmetric model of the packed-bed thermocline tank is developed. Based on the model, the cyclic thermal performance of a traditional Single-Layered and of a novel Multi-Layered Packed-Bed molten salt Thermocline Tank (SLPBTT, MLPBTT) are analyzed. First, the analysis of cyclic thermal performance of SLPBTT shows the performance can be enhanced by reducing the retention thermocline thickness. Second, this is the first time for a detailed investigation of the expanding and the shortening effects on thermocline thickness at the interface between two kinds of filler. In addition, a novel MLPBTT is designed utilizing the above interface effects for improving the performance by controlling thermocline expansion. Finally, the studies on the performance of MLPBTTs adopting three fillers (quartzite rock, cast iron, and high-temperature concrete) with different heights present that the useful energy can be increased while thermal efficiency will be reduced with the increasing cast iron's height. An optimized MLPBTT shows a significant improvement in the useful energy of 10.5% and a small drop in thermal efficiency of 2.1% in discharging process compared with those of SLPBTT using the quartzite rock. The results can be beneficial for the design and optimization of PBTT. Highlights: Cyclic thermal performance of packed-bed thermocline tank is analyzed. Effects of thermocline on performance of thermocline tank are illustrated. The expanding and shortening effects on thermocline thickness are first reported. A novel multi-layered packed-bed molten salt thermocline tank is proposed. Great rise in useful energy and small drop in efficiency of novel tank are revealed.